Chemical composition, and antioxidant and antimicrobial activities of three hazelnut (Corylus avellana L.) cultivars. - Oliveira, Ivo (2008)
Hazelnut (Corylus avellana L.) is a very popular dry fruit in the world being consumed in different form and presentations. In the present work, three hazelnut cultivars (cv. Daviana, Fertille de Coutard and M. Bollwiller) produced in Portugal, were characterized in respect to their chemical composition, antioxidant potential and antimicrobial activity. The samples were analysed for proximate constituents (moisture, fat, crude protein, ash), nutritional value and fatty acids profile by GC/FID. Antioxidant potential was accessed by the reducing power assay, the scavenging effect on DPPH (2,2-diphenyl-1-picrylhydrazyl) radicals and b-carotene linoleate model system. Their antimicrobial capacity was also checked against Gram positive (Bacillus cereus, B. subtilis, Staphylococcus aureus) and Gram negative bacteria (Pseudomonas aeruginosa, Escherichia coli, Klebsiella pneumoniae) and fungi (Candida albicans, Cryptococcus neoformans). Results showed that the main constituent of fruits was fat ranging from 56% to 61%, being the nutritional value around 650 kcal per 100 g of fruits. Oleic was the major fatty acid varying between 80.67% in cv. F. Coutard and 82.63% in cv. Daviana, followed by linoleic, palmitic, and stearic acids. Aqueous hazelnut extract presented antioxidant activity in a concentration-dependent way, in general with similar behaviour for all cultivars. Hazelnut extracts revealed a high antimicrobial activity against Gram positive bacteria (MIC 0.1 mg/ mL) showing a good bioactivity of these fruits.